2016
DOI: 10.1007/s00114-016-1397-5
|View full text |Cite
|
Sign up to set email alerts
|

Defenses against keratinolytic bacteria in birds living in radioactively contaminated areas

Abstract: Microorganisms have shaped the evolution of a variety of defense mechanisms against pathogenic infections. Radioactivity modifies bacterial communities and, therefore, bird hosts breeding in contaminated areas are expected to adapt to the new bacterial environment. We tested this hypothesis in populations of barn swallows (Hirundo rustica) from a gradient of background radiation levels at Chernobyl and uncontaminated controls from Denmark. Investment in defenses against keratinolytic bacteria was measured from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…We have previously demonstrated that birds from heavily radioactively contaminated areas were those more resistant to feather degradation by keratinolytic bacteria [28]. Microbial communities in Chernobyl are altered and the phenotypic condition of hosts has deteriorated as a consequence of the nuclear accident (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that birds from heavily radioactively contaminated areas were those more resistant to feather degradation by keratinolytic bacteria [28]. Microbial communities in Chernobyl are altered and the phenotypic condition of hosts has deteriorated as a consequence of the nuclear accident (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…Although individuals of the two sexes collaborate in nest building, females spend more time inside the nests (laying eggs and incubating them) than males [26]. In feathers, bacterial communities differ among the sexes [11], and also in some defences against keratinolytic degradation [28]. In addition, the investment in reproduction may be lower in contaminated than in clean areas, since barn swallows experience reduced reproductive success in Chernobyl [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, since these environmental factors likely vary among species (see above), natural selection could have favoured the evolution of characteristics that counteract or reduce feather degradation by keratinolytic bacteria in environments that are distinctive of each species (Burtt , Burtt et al , Javůrková et al ). If this was the case, we should find interspecific variation in traits functioning in preventing feathers’ wear (Burtt ) such as feather susceptibility to degradation by keratinolytic bacteria (hereafter, feather degradability) (Ruiz‐De‐Castañeda et al , , Ruiz‐Rodríguez et al ).…”
Section: Introductionmentioning
confidence: 99%